2005
DOI: 10.1097/01.bpo.0000173244.74065.e4
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Segmental Analysis of Weight-Bearing Radiographs of the Foot and Ankle for Children

Abstract: Clinical decision-making for the management of foot deformities in children is primarily based upon the analysis of weight-bearing radiographs of the foot and ankle. However, a comprehensive quantitative technique for the analysis of such radiographs has not been described. Ten radiographic measurements were developed and applied to the foot and ankle radiographs of a normal foot and ankle in 60 children (mean age 10 years, range 5-17 years). Intraobserver variability and interobserver variability were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
153
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 203 publications
(163 citation statements)
references
References 26 publications
7
153
2
1
Order By: Relevance
“…Lee et al [14] demonstrated that fibular overgrowth is present in achondroplastic children between 8 and 11 years of age, which leads to limitation of eversion of the hindfoot. Furthermore, the mean values of tibiotalar angle and talocalcaneal angle in our patients were less than those in the literature [4] (p \ 0.001). That the mean tibiotalar angle value was negative indicated the varus alignment of the ankle.…”
Section: Discussioncontrasting
confidence: 84%
See 4 more Smart Citations
“…Lee et al [14] demonstrated that fibular overgrowth is present in achondroplastic children between 8 and 11 years of age, which leads to limitation of eversion of the hindfoot. Furthermore, the mean values of tibiotalar angle and talocalcaneal angle in our patients were less than those in the literature [4] (p \ 0.001). That the mean tibiotalar angle value was negative indicated the varus alignment of the ankle.…”
Section: Discussioncontrasting
confidence: 84%
“…Compared with existing literature-based values [4], the mean values of all 10 measurements had a significant difference (p \ 0.01; Table 3). …”
Section: In Termsmentioning
confidence: 54%
See 3 more Smart Citations